ANALISIS STRUKTUR FISIK PUISI “KANGEN” KARYA W. S RENDRA - Deri Saputra; Sandi Ferdiansyah; Yusep Ahmadi F; Rosi Rosi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Literary work is the representative or outpouring of the heart of an author, can be poured in the form of oral and written. Poetry is the disclosure of ideas, ideas, or feelings of the heart using figurative language. Writing poetry is usually used to criticize or express an event. In poetry there is a physical structure and an inner structure. The author chose the poem by W. S Rendra entitled "Kangen" to be a research, it intends to know the physical structure of the poem. Both in terms of diction, Imaji, concrete words, figurative language, rhyme, and face. This research uses descriptive method, aims to make the description systematically, factually, and accurately about the physical structure of poetry. The physical structure of W.S Rendra's heartache is very different from the writing of poetry in general, W. S Rendra packs his poems freely with figurative words and diction choices that come out of the romantic path,